The effect of digital marketing transformation trends on consumers' purchase intention in B2B businesses: The moderating role of brand awareness - Nguyen Ngoc Hien; Tran Nguyen Huynh Nhu (Cogent Business & Management, 2022)
Digital marketing transformation is one of the important elements in a business's long-term plan. Furthermore, choosing the most optimizing and suitable marketing strategy is not really simple with B2B enterprise. Based on the theory of planned behavior and the theory of consumer behavior, this study aims to explain the effects digital marketing forms on customer attitudes toward digital marketing and purchase intention. Research sample with a size of 210 potential customers, from the important people in the B2B purchasing chain at the enterprise. After being tested through partial least squares structural equation modelling techniques, resulted in 3 out of 4 digital marketing forms were rated as important and appropriate. Furthermore, the study also explored that brand awareness only moderates the relationship between attitude toward digital marketing and customer purchase intention. The results would help managers have the right direction for the business strategy to adapt and develop the business despite any difficult circumstances.
Keywords: 650; B2B enterprises; brand awareness; customers attitude; Digital marketing; purchase intention